A structural equation modelling analysis: interprofessional team collaboration, organizational career management, and post competency of community nurses - Li Ma; Xinwei Wang; Shiyue Zou; Min Lin; Shi Qiu; Weimin Li (BMC, 2023)
Abstract Background With the advent of an ageing society and an increase in the prevalence of chronic diseases, the role of primary health care has become increasingly important and reliant on multidisciplinary collaboration. As members of this interprofessional cooperative team, community nurses play a dominant role. Thus, the post competencies of community nurses study deserve our attention. In addition, organizational career management can affect nurses in some ways. This study aims to examine the current situation and relationship among interprofessional team collaboration, organizational career management and post-competency of community nurses. Methods A survey was conducted among 530 nurses in 28 community medical institutions from November 2021 to April 2022 in Chengdu, Sichuan Province, China. Descriptive analysis was used for analysis, and a structural equation model was used to hypothesize and verify the model. A total of 88.2% of respondents met the inclusion criteria and did not meet the exclusion criteria. The main reason nurses gave for not participating was that they were too busy. Results Among the competencies on the questionnaire, ensuring quality and helping roles scored the lowest. The teaching-coaching and diagnostic functions played a mediating role. Nurses with greater seniority and those who were transferred to administrative departments had lower scores, and the difference was statistically significant (p < 0.05). In the structural equation model, CFI = 0.992 and RMSEA = 0.049, which shows that the model fit well, suggesting that organizational career management had no statistically significant effect on post competency (β = -0.006, p = 0.932) but that interprofessional team collaboration had a statistically significant effect on post competency (β = 1.146, p < 0.001) and organizational career management had a statistically significant effect on interprofessional team collaboration (β = 0.684, p < 0.001). Conclusions Attention should be given to the improvement of community nurses' post competency in ensuring quality and performing helping, teaching-coaching, and diagnostic roles. Moreover, researchers should focus on the decline in community nurses' abilities, particularly for those with greater seniority or in administrative roles. The structural equation model shows that interprofessional team collaboration is a complete intermediary between organizational career management and post competency.